Acute effects of short duration maximal endurance exercise on lipid, phospholipid and lipoprotein levels - Sgouraki, E.; Tsopanakis, A.; Kioussis, A.; Tsopanakis, C. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The acute effects of maximal endurance exercise (15 min) on lipid and lipoprotein levels were examined, in order to determine whether the level of response produced could be affected by maximal exercise intensity (incremental stress test). METHODS: Participants in this cross sectional study were male athletes (n=78) of national level: basketball (n=10), swimming (n=9), long distance (LD) running (n=23) and wrestling (n=35); also a group of non-athlete volunteers as controls (n=19). Athletes had trained an average of 3 h/day and 5 years. The ergometric test used for the determination of maximal oxygen uptake on a treadmill was based on a stepwise stress protocol. RESULTS: Immediately after a maximal effort all groups (controls included) showed significant increases in total cholesterol (TC), triglycerides (TG), phospholipids (PL) and high-density cholesterol (HDL-C), from rest values. Low-density cholesterol (LDL-C) increased significantly in basketball, LD running and wrestling, while it did not change significantly in swimming and controls, after maximal effort. Hemoconcentration was of the order of +12.5%. CONCLUSIONS: The level of these increases might be directly related to the intensity and duration of exercise performed. Acute endurance exercise (100% VO(2max)) may induce acute modification of the above lipid parameters potentiating the systematic chronic exercise effects already present.